1996
DOI: 10.3109/02813439608997080
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic widespread musculoskeletal complaints and thyroid autoimmunity: Results from a community survey

Abstract: The association between chronic widespread musculoskeletal pain complaints and thyroid antibodies in women may reflect a subgroup of patients in which thyroid autoimmunity, rather than thyroid function, is important. A possible relationship to fibromyalgia is discussed as well as a hypothetical role for thyrotropin releasing hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…For example, Bazzichi et al [22] found comorbidity with and higher levels of symptoms of fibromyalgia in patients with Hashimoto’s thyroiditis and subclinical hypothyroidism, in contrast to patients with nonautoimmune subclinical hypothyroidism. Additionally, in a population-based study, a higher prevalence of TPOAb positivity was found in respondents with musculoskeletal complaints, compared to those without [24]. An interesting study supposed a possible mechanism of action: Marquez et al [25] found microvascular alterations similar to those observed in other autoimmune diseases in skeletal muscle from patients with autoimmune thyroiditis, independent of thyroid function.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Bazzichi et al [22] found comorbidity with and higher levels of symptoms of fibromyalgia in patients with Hashimoto’s thyroiditis and subclinical hypothyroidism, in contrast to patients with nonautoimmune subclinical hypothyroidism. Additionally, in a population-based study, a higher prevalence of TPOAb positivity was found in respondents with musculoskeletal complaints, compared to those without [24]. An interesting study supposed a possible mechanism of action: Marquez et al [25] found microvascular alterations similar to those observed in other autoimmune diseases in skeletal muscle from patients with autoimmune thyroiditis, independent of thyroid function.…”
Section: Discussionmentioning
confidence: 94%
“…If headache reduces TSH, lower TSH may also be anticipated in other patient groups with pain. However, no difference in TSH was detected between persons with and without chronic musculoskeletal complaints in a Norwegian community survey (Aarflot and Bruusgaard, 1996), but few other epidemiological studies have measured TSH in pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of autoantibodies is higher in patients with neuromuscular complaints than in patients without neuromuscular complaints 7. In contrast, there is no significant relationship between thyroid function or the presence of thyroid autoantibodies in patients with either Dupuytren's contracture or limited joint mobility 8.…”
Section: Introductionmentioning
confidence: 89%